Growth of Aechmea fasciata plants in function of substrate base saturation and fertirrigation methods - Sanches, Luiz Vitor Crepaldi; Ludwig, Fernanda; Bôas, Roberto Lyra Villas [UNESP]; Mateus, Caroline de Moura D'Andréa [UNESP] (Lepidus Tecnologia, 2017)
Bromeliads are plants that have a high variability in the fertilization possibilities. This is due to the capacity of absorption of water and nutrients by their foliar trichomes and root system. This research was conducted with the objective to evaluate the development of Aechmea fasciata plants according to the substrate base saturation and the application methods of the nutritive solution. The experiment was conducted in a greenhouse with light intensity between 8,000 and 9,000 Lx. The experimental design was a randomized block design with a factorial statistical arrangement 2x5 factorial (2 percentages of substrate base saturation x 5 combinations between the methods of fertirrigation) with 4 repetitions and 7 plants by portion. The substrate base saturation (V%) established was from 20% to 40% and the fertirrigation was provided by a leaf cistern and directly in the substrate, following these proportions: 100% leaf cistern, 75% leaf cistern and 25% substrate, 50% leaf cistern and 50% substrate, 25% leaf cistern and 75% substrate and 100% substrate. The plants were conducted in vase number 11, 15 and 17, and in each change of vases, it was evaluated the plant height, the rosette diameter, the stalk diameter, the number of leaves and the leaf width. The dry phytomass and leaf area were determined in the vase changes 15 and 17. Moreover, the root exploration and the inclination degree of the plants were determined in the end of the cultivation in vase 17. As conclusion, substrate base saturation greater than 20% damages the growth of Aechmea fasciata plants. The best development of the aerial and root part of Aechmea fasciata plants were achieved when 75% of the nutritive solution is applied via cistern and 25% via substrate.
Keywords: Bromeliads; Leaf fertilization; Substrate